2017
DOI: 10.18632/oncotarget.19430
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria sustain store-operated currents in colon cancer cells but not in normal colonic cells: reversal by non-steroidal anti-inflammatory drugs

Abstract: Tumor cells undergo a critical remodeling of intracellular Ca2+ homeostasis that contribute to important cancer hallmarks. Store-operated Ca2+ entry (SOCE), a Ca2+ entry pathway modulated by mitochondria, is dramatically enhanced in colon cancer cells. In addition, most cancer cells display the Warburg effect, a metabolic switch from mitochondrial metabolism to glycolysis that provides survival advantages. Accordingly, we investigated mitochondria control of store-operated currents (SOCs) in two cell lines pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
1
14
0
2
Order By: Relevance
“…120 CRC cells exhibit remodeling of intracellular calcium homeostasis characterized by increased mitochondrial calcium storage. 121 This increased mitochondrial calcium storage was dependent on aerobic glycolysis metabolism and contributed to enhanced cell proliferation, invasion, and resistance to cell death. Further studies are needed to gain an understanding of the role of mitochondrial metabolic reprogramming, mtROS accumulation, and mitochondrial biogenesis in this progression of mitochondrial alterations during tumorigenesis.…”
Section: Gut Microbiome Signaling To Mitochondria -Ibdmentioning
confidence: 99%
“…120 CRC cells exhibit remodeling of intracellular calcium homeostasis characterized by increased mitochondrial calcium storage. 121 This increased mitochondrial calcium storage was dependent on aerobic glycolysis metabolism and contributed to enhanced cell proliferation, invasion, and resistance to cell death. Further studies are needed to gain an understanding of the role of mitochondrial metabolic reprogramming, mtROS accumulation, and mitochondrial biogenesis in this progression of mitochondrial alterations during tumorigenesis.…”
Section: Gut Microbiome Signaling To Mitochondria -Ibdmentioning
confidence: 99%
“…As mitochondria from normal and tumor cells differ because of the Warburg effect, perhaps mitochondrial control of storeoperated channels may be different as well in normal and colon cancer cells. Hernańdez-Morales et al (2017) reported recently that this is indeed the case, at least in normal and colon cancer cells. Mitochondria from normal cells are not powerful enough to remove completely the Ca 2+ -dependent inactivation of store-operated channels.…”
Section: Aspirin Nsaids and Polyamine Synthesis Blockers As Calcium mentioning
confidence: 74%
“…The huge mitochondrial potential (DY), close to −180 mV, promotes the Ca 2+ removal from cytosol into mitochondria (Valero et al, 2008;Villalobos et al, 2017), clearing large cytosolic Ca 2+ loads formed during VGCCs opening in excitable cells (Villalobos et al, 2001) or during Ca 2+ release from the ER (Rizzuto et al, 1998). In various cellular types, SOCE regulation by mitochondria depends on the Ca 2+ buffering capability of these organelles, being able to prevent the slow, Ca 2+ -dependent inactivation of Ca 2+ release activated calcium channels (CRAC) (Gilabert, 2000;Hernańdez-Morales et al, 2017). FIGURE 1 | Schematic representation of the main calcium signaling pathways through Ca 2+ channels and transporters involved in the regulation of calcium homeostasis in mammalian cells.…”
Section: Calcium Permeable Channels In Plasma Membrane Endoplasmic Rmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the σ2R agonist (F281) reduces ATP concentration in a time-and concentration-dependent manner in SK-N-SH cells, which has been attributed to its ability to interfere with the mitochondrial function, and subsequently, to attenuate ATP synthesis [24]. The regulation of SOCE by the mitochondria and vice versa have been widely described [69][70][71]. Therefore, σ2R/TMEM97 may facilitate SOCE by two different mechanisms, firstly facilitating STIM1 activation, and subsequently, favoring its contact to Orai1, but it may also enhance mitochondrial function, which would lead to mitochondrial Ca 2+ -sequestering in the proximity of the channel in the membrane that has been reported to delay the signaling of SOCE downregulation by Ca 2+ [72][73][74].…”
Section: Discussionmentioning
confidence: 99%